Pinch Analysis of Heat Exchanger Networks in A Simulated Milk Pasteurization Plant - Gelbert Jethro Sanyoto; Novita Ika Putri (Soegijapranata Catholic University, 2025)
The dairy industry depends on milk pasteurization to achieve both product safety and nutritional value through its controlled heat treatment process. However, due to substantial energy usage, finding new methods which will boost operational efficiency is required. The research investigates the Heat Exchanger Network (HEN) of a conventional milk pasteurization facility through pinch analysis to minimize energy usage and production expenses. A High Temperature Short-Time (HTST) pasteurization system was simulated in SuperPro Designer v9.0 using data obtained from an existing plant with a capacity of 4,500 kg per hour. The hot and cold stream interactions were then analyzed using HINT v2.2 to find the pinch points and help redesign the heat recovery system. The analysis resulted in two enhanced HEN configurations which became Alternative A and B. The analysis showed Alternative B provided the optimal solution between heat recovery and cooling demand requirements which would result in 2,200 annual utility cost savings. The 427,000 capital requirement may extend the payback period but its success depends on particular factors which include local energy expenses and operational efficiency. The research demonstrates that pinch analysis provides essential value for dairy processing operations because it helps improve energy efficiency and enables better sustainable decision-making.